Analysis of Environmental Health Risks of Cement Dust in Cement Grinding and Packing - Susanti, Widia Eka; Faisya, Achmad Fickry; Novrikasari, Novrikasari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The cement industry has the potential to cause dust as contamination or pollution in the air. Dust generated from the cement production process can be a health threat to cement industry workers. This study aims to assess the magnitude of the environmental health risk of cement dust exposure in the Cement Grinding and Packing section of PT X. This research is a quantitative descriptive study with the approach used is the Environmental Health Risk Analysis (ARKL). The number of sampling points in this study was 20 sampling points with a sample of 62 workers with a sample selection technique using a purposive sampling method with the criteria that workers have worked for at least 1 year. The results showed that the highest dust concentration was 0.84 mg/m3 and the lowest was 0.04 mg/m3. The dust concentration is still below the Threshold Limit Values (TLVs) which is 1 mg/m3. The results of the Environmental Health Risk Analysis (ARKL) indicate that more than a portion of the dust RQ value showed below 1 (RQ less than 1) and there are still RQ values showed above 1 (RQ more than 1) in some workers. The risk of a lifetime with a calculation of a work period of 30 years results in the majority of dust RQ value showed above 1 (RQ more than 1).Abstrak: Industri semen memiliki potensi menimbulkan debu sebagai kontaminasi atau pencemaran di udara. Debu yang dihasilkan dari proses produksi semen dapat menjadi ancaman kesehatan bagi pekerja industri semen. Penelitian ini bertujuan untuk menilai besaran risiko kesehatan lingkungan paparan debu semen di bagian Cement Grinding and Packing PT X.Penelitian ini merupakan penelitian deskriptif kuantitatif dengan pendekatan yang digunakan adalah Analisis Risiko Kesehatan Lingkungan (ARKL). Jumlah titik sampling pada penelitian ini sebanyak 20 titik sampling dengan sampel pekerja sebanyak 62 pekerja dengan teknik pemilihan sampel menggunakan metode purposive sampling dengan kriteria pekerja telah bekerja minimal 1 tahun. Hasil penelitian menunjukkan bahwa konsentrasi debu tertinggi yaitu 0,84 mg/m3 dan terendah yaitu 0,04 mg/m3. Konsentrasi debu tersebut masih dibawah Nilai Ambang Batas (NAB) yaitu 1 mg/m3. Hasil Analisis Risiko Kesehatan Lingkungan (ARKL) menunjukkan bahwa lebih dari sebagian nilai RQ debu masih berada di bawah 1 (RQ kurang dari 1) dan masih terdapat nilai RQ lebih dari 1 (RQ lebih dari 1) pada beberapa pekerja. Besar risiko lifetime dengan perhitungan masa kerja 30 tahun didapatkan hasil sebagian besar RQ debu berada di atas 1 (RQ lebih dari 1).